Artificial Intelligence: Methodology, Systems, and Applications - Dochev, Daniel (Springer, 2017)
This book constitutes the refereed proceedings of the 13th International Conference on Artificial Intelligence: Methodology, Systems, and Applications, AIMSA 2008, held in Varna, Bulgaria in September 2008.